The Effects of Turbulence on Jet Stability and the Flame Transfer Function in a Lean-burn Combustor. Issue 11 (1st November 2020) - Treleaven, N. C. W.; Garmory, A.; Page, G. J.
ABSTRACT: Large eddy simulations show that the penetration of the central jet in a multi-passage lean burn and liquid fueled combustor is dependent on the turbulence levels in the three air-flow passages of the injector. These simulations are performed using an incompressible method where an unsteady boundary condition is applied to the inlets of a truncated domain which only includes the domain downstream of the fuel injector using the recently developed Proper Orthogonal Decomposition Fourier Series method. The fluctuating inlets are built from a combination of compressible URANS data and incompressible LES data. This incompressible method is shown to be consistent with fully compressible simulations whilst requiring only one third of the computing time. Neglecting the turbulence generated in the passages results in the incorrect penetration of the central jet, resulting in a flame transfer function with a similar gain but with a different phase. Furthermore, large scale helical modes, previously detected in non-reacting simulations of a similar burner geometry are seen to be imprinted onto the liquid fuel spray, mixture fraction and heat release fields. This shows that coupling between hydrodynamic instabilities and thermoacoustic instabilities in liquid fueled engines may be more significant than suggested by previous studies of gas fueled engines.